1977
DOI: 10.1111/j.1365-3180.1977.tb00477.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of foliar absorption and translocation of 2,4‐D and 2,4,5‐T

Abstract: Summary: This review is restricted to an examination of the literature on the environmental and chemical factors that affect foliar absorption and translocation of 2,4‐dichlorophenoxyacetic acid (2,4‐D) and 2,4,5‐trichloro‐phenoxyacetic acid (2,4,5‐T) by plants. Most of the papers covered by this review have been published since 1965. Earlier works have been reviewed elsewhere by other authors (Currier & Dybing, 1959; Sargent, 1965; Franke, 1967; Robertson & Kirkwood, 1969; Hull, 1970). Often absorption and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…There are surprisingly few reports in the literature about the effects of different adjuvants on the foliar uptake of 2,4-D or any of its salts and derivatives (see review by Richardson, 1977). Sharma & Vanden Born (1970) found that addition of 1% 'Atlox 210' (a non-ionic surfactant blend of unspecified composition) caused substantial increases in the penetration of the dimethylamine salt and ethyl ester of the herbicide into Populus tremuloides leaves.…”
Section: Discussionmentioning
confidence: 99%
“…There are surprisingly few reports in the literature about the effects of different adjuvants on the foliar uptake of 2,4-D or any of its salts and derivatives (see review by Richardson, 1977). Sharma & Vanden Born (1970) found that addition of 1% 'Atlox 210' (a non-ionic surfactant blend of unspecified composition) caused substantial increases in the penetration of the dimethylamine salt and ethyl ester of the herbicide into Populus tremuloides leaves.…”
Section: Discussionmentioning
confidence: 99%
“…The improved control in 2003 was probably due to higher air temperatures 24 to 72 h after application (Fig. 1), as absorption and translocation of broadleaf herbicides increase with temperature (8).…”
Section: December Ground Ivy Covermentioning
confidence: 99%
“…higher rather than the lower, relative humidity may be associated with the rate of glyphosate absorption (Jordan, 1977;Wills, 1978), where high relative humidity delayed the drying of spray deposits on the plant surface (Richardson, 1977;Cudney, 1987), thereby prolonging the period for spray absorption. That slower drying prolongs the absorption of glyphosate has been shown in other species (Sharma & Vanden Born, 1970).…”
Section: In¯uence Of Relative Humidity On Glyphosate Activitymentioning
confidence: 99%